Risky Business - Brickman, Paul, 1949-; Pinchot, Bronson, 1959-; Curtis Armstrong; Joe Pantoliano; Nicholas Pryor; Rebecca De Mornay; Richard Masur; Tom Cruise (USA Geffen Pictures, 1983)
A suburban Chicago teenager's parents leave on vacation, and he cuts loose. An unauthorised trip in his father's Porsche means a sudden need for lots of money, which he raises in a creative way.
A Chicago teenager is looking for fun at home while his parents are away, but the situation quickly gets out of hand.
Paul Brickman
Languages : English, German, Spanish Subtitles : English, Turkish, German, French, Spanish, Italian, Russian, Czech, Dutch, Serbo-Croatian, Portuguese, Danish, Finnish, Greek, Hindi, Hungarian, Icelandic, Norwegian, Polish, Romanian, Swedish, Arabic, Bulgarian, Hebrew
Keywords: Crime; Comedy